FUNGSI DESK EDITOR SEBAGAI GATEKEEPER PADA PROGRAM BERITA LINTAS SULTENG DAN RAGAM INFO SULTENG LPP RRI PRO 1 PALU - Abubakar, Tri Reza Aditya Kasmad (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2020)
The aim of this research is to determine the function of the desk editor in determining the suitability of news at LPP RRI Palu and to find out the factors that hinder the desk editor in carrying out its function at LPP RRI Palu. The research method used is qualitative research with the research location at the LPP RRI Palu office. The informants in this research were 5 (five) informants selected through purposive sampling. Data collection techniques were carried out using participant observation and in-depth interviews. The data analysis technique uses qualitative data analysis. The research results show that when viewed from the function of the LPP RRI Palu desk editor, it is based on four stages of the gatekeeper function, namely: Broadcasting actual information from various categories such as Political, Legal and Security Affairs, Equality, Social Welfare, Culture and Sports by prioritizing the speed of the information to reach listeners. However, in practice it does not broadcast actual news and in reality, there is still some exactly the same news or information being broadcast again at different times. At the stage of expanding the quantity of information, the LPP RRI Palu editor's desk in the news sector developed information or news, but only the title changed, while the content or point of view of the news broadcast on the Ragam Info Central Sulawesi program to the Lintas Central Sulawesi program was exactly the same. Then, at the stage of interpreting the information, the LPP RRI Palu desk editor in the field of reporting pays attention to the use of sentences that are not long-winded, but which are easy to understand or more communicative so that what is meant to be conveyed is also the meaning received by the listener.